Urban Nature Experiences Reduce Stress in the Context of Daily Life Based on Salivary Biomarkers - Hunter, MaryCarol R.; Gillespie, Brenda W.; Chen, Sophie Yu-Pu (Frontiers in Psychology, 2019)
Stress reduction through contact with nature is well established, but far less is known about the contribution of contact parameters – duration, frequency, and nature quality. This study describes the relationship between duration of a nature experience (NE), and changes in two physiological biomarkers of stress - salivary cortisol and alpha-amylase. It is the first study to employ long-term, repeated-measure assessment and the first evaluation wherein study participants are free to choose the time of day, duration and the place of a nature experience in response to personal preference and changing daily schedules. During an 8-week study period, 36 urban dwellers were asked to have a nature experience, defined as spending time in an outdoor place that brings a sense of contact with nature, at least 3 times a week for a duration of 10 minutes or more. Their goal was compliance within the context of unpredictable opportunity for taking a nature pill. Participants provided saliva samples before and after a nature experience at 4 points over the study period. Before-NE samples established the diurnal trajectory of each stress indicator and these were in line with published outcomes of more closely controlled experiments. For salivary cortisol, an NE produced a 21.3%/hour drop beyond that of the hormone’s 11.7% diurnal drop. The efficiency of a nature pill per time expended was greatest between 20 and 30 minutes, after which benefits continued to accrue, but at a reduced rate. For salivary alpha-amylase, there was a 28.1%/hour drop after adjusting for its diurnal rise of 3.5% /hour, but only for participants that were least active– sitting or sitting with some walking. Activity type did not influence cortisol response. The methods for this adaptive management study of nature-based restoration break new ground in addressing some complexities of measuring an effective nature dose in the context of normal daily life, while bypassing the limitations of a clinical pharmacology dose-response study. The results provide a validated starting point for healthcare practitioners prescribing a nature pill to those in their care. This line of inquiry is timely in light of expanding urbanization and rising healthcare costs.